Unilever Group : equity valuation - Pires, Susana Sofia Castelo (2015)
The following dissertation has the purpose to value the Unilever Group, but more specifically Unilever N.V. being publicly traded in the Amsterdam Exchange Index. Unilever is seen as a global player and one of most successful and competitive fast-moving consumer goods companies. In order to valuate Unilever’s equity, a Discounted Cash Flow (DCF) approach is first carried out, since it is believed to be the most reliable methodology. The value estimated was €36.39, advising one to buy its shares when comparing to the actual price of € 31.86. Further on, a relative valuation (selecting a specific peer group and applying multiples) is suggested, as a complementary analysis to the DCF, leading to a target price of €34.15 using a forward enterprise-value multiple for 2014. Meaning, once again, a buy recommendation is issued, since the market currently yields a lower value. As a final assessment and basing the target price on the present value of future dividends, a Dividend Discount Model (DDM) is performed. This model indicates Unilever’s is priced at €18.65, leading to an overvalued market price and, consequently, a selling opportunity. Lastly, a comparison is made between these results and the target price reached by a JP Morgan’s analyst, being the last one priced at €27.00 using a DCF-WACC methodology (representing a selling opportunity). All details are further addressed in this Thesis.